Comparison of equations used to estimate soot agglomerate absorption efficiency with the Rayleigh-Debye-Gans approximation. (March 2021) - Lapuerta, Magín; González-Correa, Sofía; Cereceda-Balic, Francisco; Moosmüller, Hans
Highlights: Absorption efficiency equations for soot particles in Rayleigh regime were compared. Errors were quantified for the application of the Rayleigh-Debye-Gans approximation. Large primary particles lead to unacceptable errors at short wavelengths. Fourth-order equation by Bohren-Huffman provided the lowest errors. Wavelength spectrum and particle sizes should be considered to select equation. Abstract: The contribution of soot aerosols to radiative forcing and climate change depends on their optical properties. Since these aerosols are agglomerates composed of quasi-spherical primary particles (usually small with respect to the radiation wavelength), their properties can be calculated following the Rayleigh-Debye-Gans approximation, which considers primary particles as independent absorbers and scatterers, with corrections made to account for multiple scattering and absorption within the agglomerate. A variety of equations can be used for particles small compared to the wavelength. In this study, results of the Rayleigh, Bohren and Huffman, simplified Bohren and Huffman, and Dobbins and Megaridis equations have been compared to the results from the exact Mie equations for the absorption efficiency. This comparison has been made for individual particles with different diameters and for an ensemble of primary particles composing an agglomerate. It has been shown that some of the largest primary particles of a typical agglomerate may not behave as Rayleigh absorbers at short wavelengths, contributing to errors in the estimation of the absorption efficiency. Both Bohren and Huffman and Dobbins and Megaridis equations are useful to extend the application range of the Rayleigh equation, thus reducing the accumulated error in the estimation of the agglomerate absorption efficiency. This analysis has been performed for several complex refractive index spectra. To choose the best equation for a particular application, the wavelength spectrum of the radiation and the range of primary particle sizes should be considered, aiming for a compromise between simplicity and accuracy.